Decreased sexual function in partners after patients' first-time myocardial infarction. (1st August 2018) - Arenhall, Eva; Eriksson, Mats; Nilsson, Ulrica; Steinke, Elaine E; Fridlund, Bengt
Abstract: Background: A myocardial infarction event affects not only patients but also partners, although how it affects the partners' sexual function is not studied. Aim: The purpose of this study was to describe and compare how partners experienced their sexual function one year before with one year after first-time myocardial infarction of their partner. Methods: A longitudinal and comparative design was used. Self-reported data on Watts Sexual Function Questionnaire was collected retrospectively at two occasions from 123 partners (87 women and 36 men), measuring the year prior to the first-time myocardial infarction and the year after. Data were analysed using descriptive and inferential statistics. Results: The total score for Watts Sexual Function Questionnaire showed a significant decrease over time. In all four subscales a decrease was found, which were statistically significant in three out of the four subscales (sexual desire, 19.39 vs 18.61; p< 0.001, orgasm, 14.11 vs 13.64; p= 0.027 and satisfaction, 12.61 vs 12.31; p =0.042). Twenty-six partners reported that their intercourse frequencies decreased over time, while six partners reported an increased intercourse frequency. Conclusions: Partners' sexual function decreased after patients' first-time myocardial infarction. It is important for health personnel to offer information and discussion about sexual function and concerns with both patients and partners after a first-time myocardial infarction.